Przyczyny zmian w odpływie rzecznym na obszarach objętych wpływem eksploatacji węgla brunatnego = Couses of changes in fluvial run-off in areas affected by opencast lignite mines - Wachowiak, Grzegorz; Kępińska-Kasprzak, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Hydrological-meteorological research carried by IMGW in the area affected by the open cast lignite mine and power plant in the Bełchatów region allowed to estimate the causes of anthropogenic and natural impacts on the fluvial runoff in the area under anthropopressure. The necessity to conduct broad hydrological and meteorological research at all phases of opencast mining operations was strongly recommended.
Keywords: górnictwo odkrywkowe; lej depresyjny; antropopresja; odpływ; klimatyczny bilans wodny; opencast mining; depression cone; anthropopressure; discharge; climatic water balance